STUDI TENTANG LAJU RESPIRASI BIOTA PERAIRAN - Santoso, Arif Dwi (Jurnal Hidrosfir Indonesia, 2006)
The respiration rate of Hump back grouper (Cromileptes altivalis) and TigerGrouper (Epinehelus fuscogutattus) were measured in the laboratory usingfish-chamber to determine how deferent among them and how these wereaffected by body weight. Results showed body weight influenced respirationrates and there are variation of studied respiration levels between Humpback grouper and Tiger Grouper. Respiration rate of Hump back and Tigergrouper were 534,2 mgO2/h and 421,4 mgO2/h respectively. The functionsfor correlation between respiration of Humpback grouper and their weightwas y = 0.0065x + 0.1202 while for Tiger grouper was y = 0.0038x + 0.6108.